Towards a contemporary theory of land management - Martyn, А.; Hunko, L.; Zamlynskiy, S. (Land Management, Cadastre and Land Monitoring, 2025)
The article is devoted to the formation of the modern theory of land organisation as an independent fundamental scientific discipline through the systematic formulation of its subject and object, identification of leading theoretical models, articulation of the axiomatic basis, and organization of methodological tools capable of ensuring the transition from an ecosystem-technocratic understanding of space to its institutional-value comprehension. Building on a critical analysis of the international paradigm of land administration, Ukrainian doctrinal developments, institutional theory, property rights theory, and spatial economics, the object and subject matter of land organisation are clarified: the object is recognized as a multidimensional socio-spatial continuum in which territory is transformed into an ordered space of rights, restrictions, regimes, rents, and risks; the subject matter is the emergence, structure, and dynamics of spatial land-use regimes as a system of legal titles, servitudes (easements), zones, corridors, and reservations in multi-layer (surface–subsurface space–air column) and multi-temporal dimensions. An axiomatic core of the theory of contemporary land organisation is formulated. It is shown that land organisation methodology should include institutional analysis, theoretical-legal dogmatics of spatial regimes, spatial-economic modelling of rents, topological and network approaches, environmental accounting, geoinformation and algorithmic modelling, scenario analysis, and procedures of spatial justice. The core of the scientific problems of land organisation theory is generalized and systematized, the solution of which is a necessary precondition for the transition from fragmented normative-technical practice to institutionally mature spatial governance. The practical significance of the results lies in creating a conceptual framework for updating educational programmes, improving cadastral and planning systems, and developing standards for managing the value of space under conditions of digitalization and the growing role of spatial justice.Keywords: land organisation theory; spatial land-use regimes; boundaries and borders; spatial value; axiomatic framework of land organisation; land administration methodology; digital cadastre; institutional design; spatial governance.
Keywords: land organisation theory; spatial land-use regimes; boundaries and borders; spatial value; axiomatic framework of land organisation; land administration methodology; digital cadastre; institutional design; spatial governance